Answer:
x = -14
Step-by-step explanation:
The expression to write in this problem is:
"the sum of x and 12 equals the sum of half of x and 5"
We have:
- The sum of x and 12 is: [tex]x+12[/tex]
- The sum of half of x and 5 is: [tex]\frac{1}{2}x+5[/tex]
So, the equation to write in this problem is
[tex]x+12=\frac{1}{2}x+5[/tex]
We solve it as follows:
1) First, we subtract [tex]\frac{1}{2}x[/tex] from both sides, and we get
[tex]x-\frac{1}{2}x+12=\frac{1}{2}x-\frac{1}{2}x+5\\\frac{1}{2}x+12=5[/tex]
2) Then, we subtract 12 from both sides:
[tex]\frac{1}{2}x+12-12=5-12\\\frac{1}{2}x=-7[/tex]
3) Now we multiply both sides by 2:
[tex]\frac{1}{2}x\cdot 2=-7\cdot 2\\x=-14[/tex]
So, this is the solution.